Single nucleotide polymorphisms in thymic stromal lymphopoietin gene are not associated with allergic rhinitis susceptibility in Chinese subjects - Zhang Yuan; Song Xiaohong; Zhao Yanming; Zhang Luo; Bachert Claus (BMC, 2012)
Abstract Background Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine, implicated in the development and progression of allergic diseases. Recent studies have demonstrated significantly increased expression and synthesis of TSLPin nasal mucosa of patients with allergic rhinitis (AR), compared with nonallergic control subjects. Also, there is significant correlation between the level of TSLP mRNA and symptom severity in AR patients. In this study, we investigated whether polymorphisms in the TSLP gene were associated with increased risk of AR in the Chinese population. Methods In a candidate gene association study, we tested 11 single nucleotide polymorphisms (SNPs) in the TSLP gene in 368 AR and 325 control adult Han Chinese subjects from Beijing. The 11 SNPs were selected from the Chinese HapMap genotyping dataset to ensure complete genetic coverage. AR was established by questionnaire and clinical examination, and blood was drawn from all subjects for DNA extraction. The PLINK software package was used to perform statistical testing. Results In the single-locus analysis of AR risk, no significant differences in allele and genotype frequencies were found between AR and control subjects. Further logistic regression analyses adjusted for age and gender also failed to reveal significant associations between AR and the selected SNPs. Similarly, analysis stratified by gender, and haplotype or diplotype did not reveal any association with AR risk. Conclusion Although TSLP presents itself as a good candidate for contributing to allergy, this study failed to find an association between specific SNPs in the TSLP gene and AR susceptibility in the Han Chinese population.